Comparison of four MRI diffusion models to differentiate benign from metastatic retropharyngeal lymph nodes - Jun Liu; Li Hua; Fei Wang; Ming Chen; Yinan Sun; Zhi Hu; Luqing Shu; Andong He; Mengxiao Liu; Qing Yang; Juan Zhu; Yinfeng Qian (European Radiology Experimental)
Abstract Background Conventional magnetic resonance diffusion-weighted imaging (DWI) and morphological features have limitations in distinguishing benign from metastatic retropharyngeal lymph nodes (RLNs). We aimed to compare the value of continuous-time random walk (CTRW), fractional-order calculus (FROC), stretched-exponential model (SEM), and conventional DWI, in combination with morphological features, for differentiating between the two groups. Methods Fifty-nine patients with 68 RLNs (23 benign and 45 metastatic) were enrolled. All patients underwent DWI with 12 b-values. Diffusion data were reconstructed using conventional DWI, SEM, FROC, and CTRW models, yielding nine parameters: apparent diffusion coefficient (ADC), distributed diffusion coefficient (DDC)SEM, αSEM, DFROC, βFROC, μFROC, DCTRW, αCTRW, and βCTRW. Diffusion parameters and morphological features were compared using Mann–Whitney U, independent sample t, or χ2 tests. Logistic regression analysis was performed to identify the best diffusion indicator for classification and to develop a multiparameter model combining morphological features. Area under the receiver operating curve (AUC) and DeLong tests were used. Results Significant differences in diffusion parameters were found between benign and metastatic RLNs, except for αCTRW (p ≤ 0.022). Benign RLNs exhibited higher ADC, DDCSEM, DFROC, and DCTRW, while metastatic RLNs had higher αSEM, βFROC, μFROC, and βCTRW. Multivariate logistic regression analysis identified βCTRW as the optimal single diffusion indicator (AUC = 0.913). The combined model of βCTRW with morphological features further improved diagnostic performance and yielded an AUC of 0.948. Conclusion βCTRW is an effective noninvasive biomarker for distinguishing between benign and metastatic RLNs. Thus, combining βCTRW with morphological features enhances diagnostic efficiency. Relevance statement This study demonstrates that βCTRW, derived from the continuous-time random walk diffusion model, when integrated with morphological features, offers a reliable, noninvasive diagnostic approach for differentiating between benign and metastatic retropharyngeal lymph nodes. Key Points Non-Gaussian diffusion metrics outperformed conventional DWI. βCTRW was the best indicator for distinguishing benign from metastatic lymph nodes. Combining βCTRW with minimal axial diameter further improved diagnostic efficiency. Graphical Abstract